Avaliação da zona parcialmente diluída em soldas de revestimento do aço ASIS 1020 e Inconel 625 - Souza, André Vieira de (2022)
Coating welding is a widely used way to coat various steel equipment with nickel-based superalloys in order to increase the surface resistance to wear and corrosion. The GMAW welding process is one of the alternatives in the production of these coatings due to the operability and efficiency that directly influence the characteristics of the weld bead. During the execution of the process it is common the formation of areas with compositional gradient that varies between the coating and the substrate called Partially Diluted Zones (PDZ). One of the possible consequences of this region is the increase in hardenability that affects the toughness of the coating, as is routinely reported in the literature. This work aims to analyze the ZPD characteristics of weld beads produced using the MIG process. The proposal is to apply a coating based on Inconel 625 on ASIS 1020 steel, varying the welding speed and torch movement. The results show that the use of a triangular weaving method, for torch movement, directly influences the formation of ZPD's in order to soften the hardness in the place. This was possible to verify through the analysis of the macro and microstructure of the beads, microhardness and chemical analysis.